Income uncertaintyand household savings in China - Marcos Chamon; Kai Liu; Eswar Prasad (Institute for the Study of Labor (IZA), 2010)
China's household saving rate has increased markedly since the mid-1990s and the agesaving profile has become U-shaped. Using a panel of urban Chinese households covering 1989-2006, we document a sharp increase in income uncertainty. While the permanent variance of household income was stable, the transitory variance rose sharply. Based on these estimates, we calibrate a buffer-stock savings model and show that rising income uncertainty and pension reforms lead younger and older households, respectively, to raise their saving rates. These two factors account for over half of the increase in China's urban household savings rate and the U-shaped age-profile of savings.
Keywords: D91; J3; E21; 330; China; household savings; income uncertainty; pension reforms; buffer-stock savings